INCREASING ENERGY EFFICIENCY OF BUILDINGS AND STRUCTURES - Daniyorbek Alijanov Dilshodovich; Sobirova Minurakhan Obidjon kizi (Лучшие интеллектуальные исследования, 2024)
Annotatsiya: This article is about the environmental impact of increasing the energy efficiency of buildings and structures. Thermal-physical properties of substances, materials and products properties (IFX) or thermal-physical characteristics (IFT) - heat conductivity, temperature conductivity, heat transfer, heat transfer coefficients, thermal resistance of heat transfer, specific volume or weight heat capacity, blackness level, saturation temperature.The biggest concern in the construction of buildings is environmental damage. The article presents information about the development and use of electricity in Uzbekistan, energy analysis in buildings and structures, and mainly about energy-efficient buildings currently being developed for buildings and structures. Current modern houses have low impact on the environment and information about measures to prevent ecological damage.